Gender Equality and Nation Branding in the Nordic Region - Larsen, Eirinn; Moss, Sigrun Marie; Skjelsbæk, Inger (Routledge Studies in Gender and Global Politics, 2021)
This book explores how gender equality, a central part of the Nordic imaginary, is used in the political communication of Nordic states. The analyses presented move beyond conventional images and discourses of Nordic gender- and women-friendliness by critically investigating how and to what extent gender equality serves nation-branding in the Nordic region. Nation-branding is an unescapable part of globalisation, which is a market-oriented process dominated by the West and predicated on the creation of winners and losers. Hence, efforts to strengthen the national brand or reputation of specific Nordic countries with the aid of gender equality as a political and symbolic value inevitably help to reinforce already established global hierarchies where the Nordics play the role of moral superpower. This book comprises scholars from various fields of specialisation, and provides evidence and understanding for the growing interaction between gender-equality policies and nation-branding in all five Nordic countries. It does so by exploring a variety of policy fields and issues including women's rights, foreign policy, rape and legislation, female quotas and business policies, in addition to the index industry. The rise of the global indexes has reproduced forceful images of the Nordic countries as frontrunners of gender equality, which indeed help the Nordic countries to further position themselves as 'best at being good'. This book will be of great interest to students and scholars of Nordic gender equality in political science, sociology, law, criminology, political psychology and history, as well as those interested in nation branding, Nordic studies and exceptionalism. The Open Access version of this book, available at http://www.taylorfrancis.com/books/e/9781003017134, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.